2009
DOI: 10.1128/iai.00297-08
|View full text |Cite
|
Sign up to set email alerts
|

Host-Pathogen Interactions ofActinobacillus pleuropneumoniaewith Porcine Lung and Tracheal Epithelial Cells

Abstract: Host-pathogen interactions are of great importance in understanding the pathogenesis of infectious microorganisms. We developed in vitro models to study the host-pathogen interactions of porcine respiratory tract pathogens using two immortalized epithelial cell lines, namely, the newborn pig trachea (NPTr) and St. Jude porcine lung (SJPL) cell lines. We first studied the interactions of Actinobacillus pleuropneumoniae, an important swine pathogen, using these models. Under conditions where cytotoxicity was abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
106
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 66 publications
(64 reference statements)
4
106
0
1
Order By: Relevance
“…As expected, pgaA expression in M2000 was similar to that seen in the rseA::Km and hns::Km mutants of S4074 T . Auger et al (2) recently showed that the pgaBC genes were upregulated in A. pleuropneumoniae following contact with porcine respiratory tract epithelial cells, indicating that biofilm formation may contribute to colonization and/or persistence of this bacterium in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, pgaA expression in M2000 was similar to that seen in the rseA::Km and hns::Km mutants of S4074 T . Auger et al (2) recently showed that the pgaBC genes were upregulated in A. pleuropneumoniae following contact with porcine respiratory tract epithelial cells, indicating that biofilm formation may contribute to colonization and/or persistence of this bacterium in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Longer loops have also been correlated with virulence in neisserial species, where commensal organisms have shorter hypervariable domains (and thus shorter loops) than pathogenic species (51). There is evidence to suggest that in a number of bacterial species the capsule can be downregulated upon contact with host cells (2,15,26) and as a consequence of phase-variable expression (4,29,43), thus allowing transient exposure of OMP adhesins. Also, blebbing of outer membrane vesicles has been observed in several Gram-negative bacteria (reviewed in reference 44), allowing OMPs to traverse the capsule and reach the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an acapsular serotype A1 M. haemolytica mutant was shown to have greater fibronectin-binding activity than that of the capsular parental strain, suggesting a shielding role of the capsule. In other species, CPS may be downregulated upon contact with host cells (2,15,26) or as a consequence of phase-variable expression (4,29,43), thus allowing transient exposure of outer membrane adhesins. The shielding of OMPs, including OmpA, by CPS is likely to have important implications for the function of surface proteins but has yet to be investigated in M. haemolytica.…”
mentioning
confidence: 99%
“…Following the first report of the SJPL cells (5), other investigators have used these cells in their studies (1,4,6,7; C. A. Gagnon and M. Jacques, 9 December 2008, international patent application PCT/CA2008/001953). In some of those reports, the SJPL cells were used as a model to study viral and bacterial pathogenesis in regard to the respiratory tract environment of the susceptible host (1, 7).…”
mentioning
confidence: 99%